THE RELATIONSHIP BETWEEN PARENTS' KNOWLEDGE ABOUT HIV/AIDS AND HIV/AIDS PREVENTION EFFORTS IN CHILDREN IN THE DONAN AREA, CILACAP - budiarti, tri; Kusnaeni, Ahmad; Saputra, Bejo Danang (Gamma Publishing, 2025)
Children's Background is a very valuable future investment as the nation's next generation. The quality of a child's life is very determined by the role of parents so thatparental knowledge is very important, especially in efforts to prevent HIV/AIDS in children. The purpose of knowing the relationship between parental knowledge aboutHIV AIDS and HIV/AIDS prevention efforts in children. This research method is correlational with a cross sectional approach. The sample with a total sampling of 37 parents of toddlers with primary data through a questionnaire and analyzed univariate andbivariate with chi square. The results obtained that the level of parental knowledge aboutHIV/AIDS was mostly in the poor category, which was 20 people (54.1%), HIV/AIDSprevention efforts were mostly in the poor category, namely 21 people (56.8%), theresults of bivariate analysis using the chi square p-value test method of 0.153 showed thatthe p-value was greater than the value of α = 0.05 so that Ho was accepted, This means that there is no relationship between parental knowledge of HIV AIDS and HIV/AIDSprevention efforts in children. The conclusion is that there is no relationship betweenparental knowledge about HIV AIDS and efforts to prevent HIV/AIDS in children.